Risk Mitigation Strategy In Chicken Distribution System Integration Methodsix Sigma, Root Cause Analysis Dan Swot - Mochammad Rizal; Wiwik Sumarmi; Ribangun Bambang (Procedia of Engineering and Life Science, 2022)
PT. Behaestex Pandaan is a textile company engaged in the manufacture of Muslim clothing, especially woven sarongs. Weaving sarongs made with ATBM (Not Machine Weaving Equipment) provide the best quality. On the other hand PT. Behaestex Pandaan has provided the best quality but lacks efficiency in terms of factory layout. This research seeks to help make a design proposal for the placement of work stations in order to aim at minimizing the total moment and distance of material transfer due to the condition of the work station having a total moment and distance of movement that is less effective and efficient. This study uses the method of Systematic Layout Planning (SLP) and Blockplan. There are alternative layouts that are possible and then selected to determine the most effective alternative based on the lowest total moment and material displacement distance. In the Systematic Layout Planning (SLP) and Blockplan methods there will be a comparison that can determine the effectiveness of the 2 methods. The Systematic Layout Planning (SLP) method has more granular factors such as workflow and qualitative considerations, while Blockplan is automated only considers a few factors regardless of the current workflow. From the results of this study can find solutions to the problems experienced by PT. Behaestex Pandaan about the proposed layout by comparing the results of the SLP and Blockplan methods so that it can find out the total moment and and distance of material transfer which is more effective and efficient at PT. Behaestex Pandaan.